2022
DOI: 10.1002/pc.27106
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on behaviors of composite laminates with initial delamination defects under impact and compression after impact

Abstract: The initial delamination defects may arise during the preparation of carbon fiber-reinforced polymer (CFRP) composite laminates, so its effects need to be considered in the evolution of mechanical properties. In this article, the behaviors of composite laminates with initial delamination defects under impact and compression after impact (CAI) are investigated by numerical method. The simulation framework composed of the micromechanics of failure (MMF) theory and the mixed mode exponential cohesive zone model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In addition, with regard to the morphology of the subsurface damage at the front and rear surface as seen from the thermal images, it was concluded that the damage could prevail across several laminas, which is consistent with findings from other reports. [ 21,30,31 ] Altogether, these may have practical implications during inspection: for a given barely visible damage observed at the impacted surface, the subsurface damage in a thick laminate could be much more extensive compared to a thin laminate. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, with regard to the morphology of the subsurface damage at the front and rear surface as seen from the thermal images, it was concluded that the damage could prevail across several laminas, which is consistent with findings from other reports. [ 21,30,31 ] Altogether, these may have practical implications during inspection: for a given barely visible damage observed at the impacted surface, the subsurface damage in a thick laminate could be much more extensive compared to a thin laminate. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…As a result, regarding various types of composite laminates, many studies have been carried out to illuminate the impact damage mechanism as well as the deep negative effect of the LVI on the subsequent mechanical properties such as tensile test, [10] shearing, [11,12] bending [13][14][15][16] and compressive test. [17][18][19] The part of existing latest related research and their research contents are summarized and the first point to note is that even a tiny impact energy can lead to a significant decrease in the strength under various kinds of post-impact tests. In addition, the effect of LVI load on the post-impact behavior depends on a combination of multiple factors, such as original materials, the configuration of the specimens, and even size, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experiments have shown that the stacking sequence would affect the damage initiation and propagation, and damage resistance of laminates. 27,28 Cai et al 29 investigated the impact response and CAI behavior of composite laminates containing initial delamination defects by numerical simulation, and discussed the interaction between the initial delamination defects of the laminates and the impact loads. Oskay et al 21 provided a detailed investigation of the CAI response of woven E-glass fiber-reinforced vinyl ester composites.…”
Section: Introductionmentioning
confidence: 99%